2015
DOI: 10.1038/nplants.2015.167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the plastidial stringent response in plant growth and stress responses

Abstract: The regulatory nucleotide guanosine 5'-diphosphate 3'-diphosphate (ppGpp), which was originally identified in Escherichia coli, controls the expression of a large gene set and many enzyme activities. The ppGpp-dependent control of cell activities is referred to as the stringent response. Recently, genes responsible for the synthesis and degradation of ppGpp have been identified not only in bacteria, but also in eukaryotes, including plants and animals, indicating that the stringent response is, unexpectedly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(162 citation statements)
references
References 47 publications
9
144
0
Order By: Relevance
“…Overexpression lines have strong basal chlorophyll fluorescence, F0 ( Figure 1A; Supplemental Figure 3), and a reduction in the maximal efficiency (or quantum yield, QY) of photosystem II (PSII): the average quantum yield was 0.86 6 0.001 SE in wild-type plants 12 d after stratification (DAS) versus 0.690 6 0.002 SE in OX: RSH2-GFP.1, 0.69 6 0.006 SE in OX:RSH3-GFP.1, and 0.73 6 0.006 SE in OX:RSH3-GFP.2 (n = 8). During preparation of this manuscript, similar phenotypes were reported for plant lines overexpressing RSH3 (Maekawa et al, 2015). Now focusing on plants overexpressing RSH3-GFP, we confirmed that chlorophyll levels are lower than in wild-type plants and found that this is accompanied by a reduction in the chlorophyll a/b ratio ( Figure 1B).…”
Section: Results Ppgpp Regulates Global Chloroplast Functionsupporting
confidence: 67%
“…Overexpression lines have strong basal chlorophyll fluorescence, F0 ( Figure 1A; Supplemental Figure 3), and a reduction in the maximal efficiency (or quantum yield, QY) of photosystem II (PSII): the average quantum yield was 0.86 6 0.001 SE in wild-type plants 12 d after stratification (DAS) versus 0.690 6 0.002 SE in OX: RSH2-GFP.1, 0.69 6 0.006 SE in OX:RSH3-GFP.1, and 0.73 6 0.006 SE in OX:RSH3-GFP.2 (n = 8). During preparation of this manuscript, similar phenotypes were reported for plant lines overexpressing RSH3 (Maekawa et al, 2015). Now focusing on plants overexpressing RSH3-GFP, we confirmed that chlorophyll levels are lower than in wild-type plants and found that this is accompanied by a reduction in the chlorophyll a/b ratio ( Figure 1B).…”
Section: Results Ppgpp Regulates Global Chloroplast Functionsupporting
confidence: 67%
“…The lower levels of photosynthetic pigments in ppGpp + cells could be due to increased pigment degradation, decreased pigment production, or a combination of the two. Based on these results, it is likely that ppGpp + cells are less photosynthetically active than control cells (18,19).…”
Section: High (P)ppgpp Levels Stop Growth and Dramatically Alter Synementioning
confidence: 99%
“…In Arabidopsis thaliana, all of these proteins localize to the chloroplast (19,56), and ppGpp levels rise in plants in response to darkness and other stresses, including wounding (57). Two recent studies have also shown that ppGpp levels affect photosynthetic capacity and chloroplast development in Arabidopsis (19,58). Thus, it is likely that aspects of the stringent response pathway are conserved between cyanobacteria and chloroplasts.…”
Section: Conservation and Adaptation Of Stringent Response Mechanisms Inmentioning
confidence: 99%
“…9 The ppGpp effects on plant growth are the opposite of those observed in the cytosolic ppGpp overaccumulation mutant as reported here, suggesting that cytosolic and plastidial ppGpp levels could regulate plant growth in a different way. Perhaps, in the wild type plant, ppGpp levels are coordinately regulated in each location for optimizing different metabolic processes and gene expressions to adapt the growth rate in response to varying environmental conditions.…”
mentioning
confidence: 57%
“…We recently showed that Arabidopsis RSHs, localized in chloroplasts, are important for plant growth and stress responses; ppGpp overaccumulation in chloroplasts results in robust growth under nutrient-deficient conditions. 9 This indicates that the stringent response is at least operating in the organelle, which has important roles in the systematic growth of host organisms.…”
mentioning
confidence: 99%